Eco-friendly options for the management of white rust in Indian mustard under mid hill conditions of North-Western India - KUMAR*, ASHOK (Indian Phytopathology, 2009)
Field experiments were conducted from 2001-02 to 2006-07 to find out eco-friendly strategy like sowing time, varieties ; plant activators and plant extracts for management of white rust disease of Indian mustard caused by Albugo candida. Sowing time had significant impact on severity of white rust disease in mustard. Lowest severity of white rust on leaves (12.5%) and staghead infection (0.3%) was recorded in the Oct.1 sown crop. White rust on leaves and staghead infection increased with delay in sowing time. Highest seed yields of 1639kg/ha, 1593kg/ha and 1250kg/ha were obtained in the Oct. 15, Oct.1 and Oct. 15 sown crops during 2001-02, 2002-03 and 2003-04, respectively. There was a significant reduction in the severity of white rust as well as staghead infection as a result of foliar sprays of 0.02% solution of Bion 50WG (bezothiadiazole). Among the five plant extracts, the severity of white rust on leaves and staghead infection was lowest in case of Eucalyptus (18.3%, 3.7%) followed by neem (19.9%, 4.0%) and garlic (21.0%, 3.9%).